Perbandingan Evaluasi Tingkat Kerusakan Jalan Berdasarkan Metode Bina Marga dan PCI (Pavement Condition Index) pada Ruas Jalan Sampang-Ketapang STA. 23+800-29+100 Provinsi Jawa Timur - Nur Laili Hafiza; Ibnu Sholichin (KERN, 2022)
The Sampang-Ketapang road is a road that has a contribution for economic growth in Sampang because the road is a route to government agencies and several tourist attractions. The road is damaged so that it interferes with the safety of road users. Seeing the importance of the Sampang-Ketapang road, this study was conducted to evaluate the severity of the damage. The location on Sampang-Ketapang STA. 23+800 – 29+100 comparing the value of road damage conditions between two methods, Bina Marga Method and the PCI (Pavement Condition Index) method. The secondary data use CBR data and primary use LHR, documentation and dimensions of damage. The results of the comparison of the evaluation of the level of road damage based on the Bina Marga and PCI (Pavement Condition Index) methods on Sampang-Ketapang road, there are seven types of road damage with dominant damage, crack and pothole. Comparison of the value of road damage conditions according to the Bina Marga method of 5 means the road is in the category of periodic maintenance while the PCI method is 78.13 means the road is in the category of routine maintenance. The appropriate is an additional overlay with an additional pavement design thickness of 60 mm.